DOI: 10.14264/uql.2016.102
|View full text |Cite
|
Sign up to set email alerts
|

L1 adaptive control augmentation for a hypersonic glider

Abstract: ii ABSTRACTThe aim of this research is to investigate control strategies to carry out a pull out of a ballistic trajectory (initially the same as the sub-orbital ballistic HyShot and HIFiRE trajectories) and a pulsed roll angle bank manoeuvre for a hypersonic glider. This study investigates the performance of two different control methodologies in the presence of aerodynamic, gravimetric and actuator uncertainties: pole placement control (PPC) (as the baseline) and adaptive control (to augment the PPC).Through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…For an LTI system, Equations ( 22) and (25) would need only to be computed once as the matrices 𝐴 𝑚 and 𝐵 are time invariant. In the LTV case, Equations ( 22) to ( 25) must be re-computed at every adaptive step as part of the successive linearization process.…”
Section: Adaptive Lawmentioning
confidence: 99%
See 1 more Smart Citation
“…For an LTI system, Equations ( 22) and (25) would need only to be computed once as the matrices 𝐴 𝑚 and 𝐵 are time invariant. In the LTV case, Equations ( 22) to ( 25) must be re-computed at every adaptive step as part of the successive linearization process.…”
Section: Adaptive Lawmentioning
confidence: 99%
“…1) the transient performance can be known without requiring persistent excitation, 2) decoupling of robustness and adaptation rate allows for fast adaptation, and 3) a bounded time delay margin [21]. For the reasons listed, L 1 adaptive control has been implemented on aerospace systems such as quadrotors, aircraft, missiles, and hypersonic vehicles [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee et al applied an L 1 augmentation to a pole placement controller for the longitudinal dynamics of hypersonic gliders. Simulation studies found that adaptive augmentation improved control performance [19]. An optimal control modification was applied to a model reference adaptive controller (MRAC) for a fighter aircraft [20].…”
Section: Introductionmentioning
confidence: 99%